El Ritmo en la Vida - Olea-Chandía, Jorge (2020)
The concept of rhythm is connected, in the first place, with the idea of musicality, however, the values or elements of rhythm are not only qualities of temporality and melodic sound, but they also manifest themselves in other aspects, such as movement, space, nature or physiology. This essay proposes a journey through the meanings of rhythm to the experience of rhythm.